2012
DOI: 10.3354/meps09824
|View full text |Cite
|
Sign up to set email alerts
|

Trophic transfer and habitat use of oyster Crassostrea virginica reefs in southwest Florida, identified by stable isotope analysis

Abstract: Oyster reefs have been identified as essential fish habitat for resident and transient species. Many organisms found on oyster reefs, including shrimp, crabs, and small fishes, find shelter and food on the reef and in turn provide food for transient species that frequent oyster reefs. The objective of this study was to determine trophic transfer on oyster reefs in a subtropical environment using stable isotope compositions. Water, sediment, particulate organic matter, various crustaceans, fishes, as well as oy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…This lack of difference in nekton density at reefs with different physical and biological characteristics is similar to that found with other studies of artificial reefs of varying heights (Lenihan et al, 2001), Table 3 Mean stable isotope values (δ 13 C and shell density and vertical relief (Humphries et al, 2011b), and reefs with and without the presence of live oysters (Tolley and Volety, 2005;Summerhayes et al, 2009). Although ecological theory holds that structurally complex habitats are expected to sustain higher densities and more diverse communities than structurally simple ones, defining structural complexity has never been straightforward (Beck, 1998;Bartholomew et al, 2000), and it is not clear whether the harvested and nonharvested sites represented different levels of complexity or just differences in habitat characteristics. No consensus exists as to how to define oyster reef complexity; in some experiments oyster or shell density, vertical relief, or mixtures of unaggregated shells (simple) versus clusters (complex) were used, making it difficult to determine when complexity had actually changed (Grabowski and Powers, 2004;Grabowski et al, 2008;Humphries et al, 2011a).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This lack of difference in nekton density at reefs with different physical and biological characteristics is similar to that found with other studies of artificial reefs of varying heights (Lenihan et al, 2001), Table 3 Mean stable isotope values (δ 13 C and shell density and vertical relief (Humphries et al, 2011b), and reefs with and without the presence of live oysters (Tolley and Volety, 2005;Summerhayes et al, 2009). Although ecological theory holds that structurally complex habitats are expected to sustain higher densities and more diverse communities than structurally simple ones, defining structural complexity has never been straightforward (Beck, 1998;Bartholomew et al, 2000), and it is not clear whether the harvested and nonharvested sites represented different levels of complexity or just differences in habitat characteristics. No consensus exists as to how to define oyster reef complexity; in some experiments oyster or shell density, vertical relief, or mixtures of unaggregated shells (simple) versus clusters (complex) were used, making it difficult to determine when complexity had actually changed (Grabowski and Powers, 2004;Grabowski et al, 2008;Humphries et al, 2011a).…”
Section: Discussionsupporting
confidence: 80%
“…Benthic microalgae could also contribute to the food webs of oyster reef communities; however, in San Antonio Bay, Texas (also a shallow, turbid estuary), the microphytobenthos contributed less than 2% of the primary production found in the water column (MacIntyre and Cullen, 1996). Benthic macroalgae, seagrass epiphytes, and upstream terrestrial plant matter can also contribute to the basal food source (Abeels et al, 2012), but these sources were not observed within the studied reef areas.…”
Section: Figurementioning
confidence: 87%
See 2 more Smart Citations
“…habitat (Tolley and Volety, 2005;Abeels et al, 2012), decreasing coastal erosion (Meyer et al, 1997;Coen et al, 2007), and improve the surrounding water quality through the removal of suspended particulates (Officer et al, 1982;Wall et al, 2008). Finally, shellfish also provide a significant source of income and economic stimulus within coastal communities (Shumway et al, 2003;Ekstrom et al, 2015).…”
Section: Discussionmentioning
confidence: 99%